2022
DOI: 10.1158/2159-8290.cd-22-0489
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus 42 Drives Digital Papillary Adenocarcinoma and Elicits a Germ Cell–like Program Conserved in HPV-Positive Cancers

Abstract: The skin is exposed to viral pathogens, but whether they contribute to the oncogenesis of skin cancers has not been systematically explored. Here we investigated 19 skin tumor types by analyzing off-target reads from commonly available next-generation sequencing data for viral pathogens. We identified human papillomavirus 42 (HPV42) in 96% (n = 45/47) of digital papillary adenocarcinoma (DPA), an aggressive cancer occurring on the fingers and toes. We show that HPV42, so-far considered a non-oncogenic, “low-ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 67 publications
2
14
1
3
Order By: Relevance
“…5 In their article, Bui et al 18 reported a series of eight acral sweat glands tumors diagnosed as "DPA." In contrast to prior observations with a larger set of tumors 5,14,16 they claim to have identified two "DPA" groups with distinct phenotypes, genetics, and outcomes. "Group A" (n = 4) included painless slow-growing nodules microscopically characterized by small, well defined dermal tumors forming independent glandular structures.…”
contrasting
confidence: 81%
See 3 more Smart Citations
“…5 In their article, Bui et al 18 reported a series of eight acral sweat glands tumors diagnosed as "DPA." In contrast to prior observations with a larger set of tumors 5,14,16 they claim to have identified two "DPA" groups with distinct phenotypes, genetics, and outcomes. "Group A" (n = 4) included painless slow-growing nodules microscopically characterized by small, well defined dermal tumors forming independent glandular structures.…”
contrasting
confidence: 81%
“…Molecular analyses of sweat gland tumors have identified recurrent and mutually exclusive oncogenic drivers such as CRTC1/3::MAML2 in hidradenoma and their malignant counterparts 12 or BRAF mutations in tubular adenoma 13 . Recently, human papillomavirus 42 (HPV42) was discovered in DPA 5,14–17 . Indeed, DPA genome was found in 96%–100% of tested DPA tumors, 5,16 but not in any other sweat gland neoplasm or adenocarcinoma 5 …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In 2008, MCPyV was linked to Merkel cell carcinoma (MCC) 22 , and has since been identified as an etiological agent in 80% of MCC tumors 23 . Recently, HPV42, previously classified as a "low-risk" HPV type, has been found in a majority of digital papillary adenocarcinomas 24 . It is suspected that viruses may play a causative role in the pathogenesis of other cancer types 25,26 , and there may be more oncoviruses that have yet to be discovered.…”
Section: Introductionmentioning
confidence: 99%